Values and Hedonic Consumption Behavior: A Field Research in Kirikkale - Güler, Yunus Bahadır (Asian Journal of Empirical Research, 2014)
Values are among the important factors that determine how people act and are motivated. Values are related with consumption behaviors and purchasing processes, too. Recently the concept of hedonic consumption is encountered and researched often. The concept which is termed as hedonic consumption is a part of consumption explained as being happy, pleasure, sensuality or relieving. Present study investigates the relationships among individual values and hedonic consumption behavior; it is aimed to provide information to marketing practitioners and researchers about values. In this study, hedonic consumption is measured by widely used reliable and valid scales. Data is gathered by face to face survey method. Factor analysis for scales and correlation analyses for the possible relationships among values and hedonic consumption are conducted. At the study, 430 valid questionnaires are obtained. According to research, dimensions of values depicted as “benevolence”, “universalism”, “self direction”, “conformity”, “tradition”, “power”, “self security”, “spirituality”, “stimulation”, and “hedonism”, and dimensions of hedonic consumptions are; “excitement and escape”, “innovativeness” and “pleasure and fun”. As a result, it is seen that values of benevolence, self-direction, tradition, power, spirituality, stimulation and hedonism are related with hedonic consumption.